2014
DOI: 10.3906/tar-1402-60
|View full text |Cite
|
Sign up to set email alerts
|

L-arginine impact on cherry rootstock rooting and biochemical characteristics in tissue culture

Abstract: In the present study, the effects of indole-3-butyric acid (IBA) separately and simultaneously with L-arginine on the morphogenic and biochemical responses in the cherry rootstocks CAB-6P (Prunus cerasus L.) and Gisela 6 (Prunus cerasus × Prunus canescens) were investigated. In the CAB-6P rootstock, the best root number and root length results were obtained with 2 mg L -1 IBA plus 0.5 mg L -1 L-arginine and 1 mg L -1 IBA plus 1 mg L -1 L-arginine, respectively. The rooting percentage was highest (100%) with 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…More recently, a study was conducted to determine the effects of gibberellic acid (GA 3 ) and N6-benzyladenine (BA) on in vitro micrografting developed to produce P. lentiscus plantlets (Onay et al, 2016b). Furthermore, different studies have shown that cytokinins, GA 3 and some amino acids can improve cell growth and enhance organ development (Baskaran and Jayabalan, 2007;Kumar and Kumari, 2010;Unek et al, 2010;Malá et al, 2013;Gonbad et al, 2014;Sarropoulou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a study was conducted to determine the effects of gibberellic acid (GA 3 ) and N6-benzyladenine (BA) on in vitro micrografting developed to produce P. lentiscus plantlets (Onay et al, 2016b). Furthermore, different studies have shown that cytokinins, GA 3 and some amino acids can improve cell growth and enhance organ development (Baskaran and Jayabalan, 2007;Kumar and Kumari, 2010;Unek et al, 2010;Malá et al, 2013;Gonbad et al, 2014;Sarropoulou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Positive effect of IBA on rooting in vitro was found in numerous studies in different species of Prunus sp. (Buyukdemirci, 2008;Šiško, 2011;Canli and Demir, 2014;Sarropoulou et al 2014;Xu et al 2015;Kumar et al 2020;Zamanipour et al 2015). While 2,3,5-triiodobenzoic acid (TIBA) is well known as the inhibitor of polar transport of indol-acetic acid, it could, however, provoke rooting regarding site of application and concentration (McNamara and Mitchell, 1991; Kovačević et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a lot of applied research has been done to enhance adventitious rooting in difficult-to-root species, especially woody ones, by the utilization of bioactive compounds that could integrate or adjuvate the auxin activity. Cuttings have been supplemented with phenolic compounds [21], thiol compounds [22,23], amino acids [24,25], and carbohydrates [26,27] in combination with auxin to stimulate the root formation and to reduce its unfavourable side effects. In fact, it has been reported that adventitious roots may be stunted or malformed, as a result of the auxin treatment alone [28], giving rise to a poor-quality root system that will hardly support the ex vitro transfer and acclimatization.…”
Section: Introductionmentioning
confidence: 99%